Evaluation of Exchange Current Density for LSM Porous Cathode Based on Measurement of Three-Phase Boundary Length. (2nd June 2015) - Miyoshi, Kota; Miyamae, Takuma; Iwai, Hiroshi; Saito, Motohiro; Kishimoto, Masashi; Yoshida, Hideo
Abstract : Here we propose an empirical formula for the exchange current density per unit TPB (three-phase boundary) length for porous LSM (lanthanum strontium manganite) cathodes for solid oxide fuel cells, which is often required for numerical modeling of cathode performance based on reconstructed microstructures obtained with tomography techniques. Electrochemical measurement of LSM cathodes was conducted under various oxygen partial pressure (0.05-0.25 atm) and temperature (800-950 °C) conditions. The derived values were compared with those from a thin and dense patterned LSM electrode in literature, and were found to be small at 800 °C. One of the possible reasons is that the charge transfer can be occurred at not only TPB but also two-phase (LSM-Pore) boundary in the case of thin patterned electrode.